2014
DOI: 10.1056/nejmoa1312173
|View full text |Cite
|
Sign up to set email alerts
|

High versus Low Blood-Pressure Target in Patients with Septic Shock

Abstract: Targeting a mean arterial pressure of 80 to 85 mm Hg, as compared with 65 to 70 mm Hg, in patients with septic shock undergoing resuscitation did not result in significant differences in mortality at either 28 or 90 days. (Funded by the French Ministry of Health; SEPSISPAM ClinicalTrials.gov number, NCT01149278.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
629
4
22

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 936 publications
(701 citation statements)
references
References 20 publications
18
629
4
22
Order By: Relevance
“…Recently, the SEPSISPAM trial demonstrated that targeting a higher BP target is not beneficial in adults with sepsis (14). Although there is no trial evidence upon which to base practice in children, it seems counterintuitive that a child would need a higher BP centile target than an adult.…”
Section: Accm-pals Recommends Targeting 50 Th Centile Sbp For Age Apmentioning
confidence: 99%
“…Recently, the SEPSISPAM trial demonstrated that targeting a higher BP target is not beneficial in adults with sepsis (14). Although there is no trial evidence upon which to base practice in children, it seems counterintuitive that a child would need a higher BP centile target than an adult.…”
Section: Accm-pals Recommends Targeting 50 Th Centile Sbp For Age Apmentioning
confidence: 99%
“…Here, kidney function may already depend on blood flow values within a narrow range – whereas any sepsis‐related increase in CTH or reductions in RBF are likely to elicit renal failure. A randomized controlled trial comparing a mean arterial pressure (MAP) of 80–85 mmHg to one of 65–70 mmHg in septic patients demonstrated no survival benefit for the group randomized to the higher MAP, but a lower need for renal replacement therapy in patients with prior hypertension 65. We speculate that these findings may reflect the specific vulnerability to hypoperfusion of kidney medulla in patients with pre‐existing renal capillary dysfunction.…”
Section: Therapeutic Implicationsmentioning
confidence: 88%
“…Yet, so many large RCTs have been negative in critically ill patients. Whatever we test does not seem to make a difference to outcomes: the pulmonary artery catheter [1,2], intracranial pressure monitoring [3], optimal blood pressure levels in septic shock [4], central venous oxygen saturation monitoring [5], blood transfusions, and so the list goes on. We were so proud to have finally developed a drug for sepsis, drotrecogin alfa (activated) [6], but this was such an unexpected and surprising event that another study was performed, which negated the results [7] and the drug was taken off the market.…”
mentioning
confidence: 99%
“…Second, another limitation of RCTs is that the method used to induce the change under investigation can influence interpretation of the results. For example, a study on two different blood pressure levels in septic shock [4] is actually a study of two doses of norepinephrine, a drug that has its own effects. Third, in pragmatic trials, protocol design allows physicians to decide whether or not a patient should be enrolled, potentially creating problems with patient enrollment and randomization.…”
mentioning
confidence: 99%